2022
DOI: 10.1038/s41375-022-01796-7
|View full text |Cite
|
Sign up to set email alerts
|

Proteogenomic analysis of acute myeloid leukemia associates relapsed disease with reprogrammed energy metabolism both in adults and children

Abstract: Despite improvement of current treatment strategies and novel targeted drugs, relapse and treatment resistance largely determine the outcome for acute myeloid leukemia (AML) patients. To identify the underlying molecular characteristics, numerous studies have been aimed to decipher the genomic- and transcriptomic landscape of AML. Nevertheless, further molecular changes allowing malignant cells to escape treatment remain to be elucidated. Mass spectrometry is a powerful tool enabling detailed insights into pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…MS analyses have revealed LSC-specific changes in oxidative phosphorylation, adhesion molecule composition, and RNA processing properties ( 40 ). Similar findings were uncovered from in-depth proteomic studies performed on 47 adults and 22 pediatric AML samples taken throughout disease progression ( 41 ). Mitochondrial ribosomal protein and subunits of the respiratory chain complex were enriched at relapse, suggesting a role for altered energy metabolism.…”
Section: The Proteogenomic Landscape Of Solid and Liquid Tumorssupporting
confidence: 72%
“…MS analyses have revealed LSC-specific changes in oxidative phosphorylation, adhesion molecule composition, and RNA processing properties ( 40 ). Similar findings were uncovered from in-depth proteomic studies performed on 47 adults and 22 pediatric AML samples taken throughout disease progression ( 41 ). Mitochondrial ribosomal protein and subunits of the respiratory chain complex were enriched at relapse, suggesting a role for altered energy metabolism.…”
Section: The Proteogenomic Landscape Of Solid and Liquid Tumorssupporting
confidence: 72%
“…In a single-cell analysis, Li et al found that proliferating stem/progenitor-like cells were reprogrammed to a quiescent stem-like expression pattern in primary refractory AML by upregulation of CD52 and LGALS1 expression [28]. Stratmann and colleagues used mass-spectrometry-based indepth proteomics to show that at relapse, energy metabolism is reprogrammed by the enrichment of mitochondrial ribosomal proteins and subunits of respiratory chain complexes as well as higher levels of granzymes and lower levels of the anti-inflammatory protein CR1/CD35 [29].…”
Section: Aml Is Highly Heterogenousmentioning
confidence: 99%
“…Recently, proteomics profiling as part of a multi-omics approach has been used to predict neurodegeneration in children with Down’s syndrome pointing to a disruption of IGF1 signalling as a potential contributor to or biomarker to the neurodegenerative process, again potentially providing novel pathways for targeted treatments (Araya et al, 2022 ). In paediatric oncology, proteogenomic studies are furthering our understanding of relapse and treatment resistance in children with acute myeloid leukaemia, providing new approaches to predict relapse during disease progression, novel biomarkers and new targets for novel drug therapies (Stratmann et al, 2022 ). Other areas where proteomics provides value to prediction, diagnostics and personalised interventions include chronic kidney disease and peritoneal dialysis in children (Cummins et al, 2022 ; Trincianti et al, 2022 ), drug metabolism and personalised dose optimisation in children (Streekstra et al, 2021 ; van Groen et al, 2022 ) and the use of multi-omics derived biomarkers to develop prediction models in children with asthma to guide therapy (Golebski et al, 2020 ; Kang et al, 2022 ).…”
Section: Developing Biomarkers and Targeted Therapies To Treat Childh...mentioning
confidence: 99%